2004
DOI: 10.1080/00140130310001629766
|View full text |Cite
|
Sign up to set email alerts
|

Cervicobrachial muscle response to cognitive load in a dual-task scenario

Abstract: People working in an office environment often have to deal with significant cognitive workload due to the coordination of multiple, simultaneous tasks. The objective of this research was to examine the impact of cognitive load in officetype tasks on physical-stress response, using a dual-task paradigm involving a primary cognitive task and secondary typing task. The central hypothesis of this research was that altering the demands of the cognitive task would lead to a difference in physical stress-level and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…A decrease in typing performance with additional workload has been mentioned in other studies 9,17) . The prolongation of initial response time in our study is consistent with a study by Sternberg et al 43) , as they concluded that it takes a progressively longer time to initiate the response of typing a string of characters as the number of characters in the string is increased.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A decrease in typing performance with additional workload has been mentioned in other studies 9,17) . The prolongation of initial response time in our study is consistent with a study by Sternberg et al 43) , as they concluded that it takes a progressively longer time to initiate the response of typing a string of characters as the number of characters in the string is increased.…”
Section: Discussionmentioning
confidence: 91%
“…In other words, the use of meaningless character strings instead of regular words, and typing with a single finger (index finger) instead of all the fingers, made the task in this study more controlled than an automatic processing task. Controlled processing is slow, serial, conscious, and voluntary, while automatic processing such as a regular typing task would be fast, unconscious, and often involuntary, and would be invoked to perform well-developed skilled behaviors with less probability of committing error 9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, which manipulated either mental demands (e.g., Leyman et al 2004;Lundberg et al 2002) or psychological demands (e.g., Marras et al 2000), measured perceptions of the psychosocial environment indirectly through ratings of stress and perceived mental workload (Leyman et al 2004), anxiety and blood pressure (Marras et al 2000), and heart rate (Lundberg et al 2002). The current study expands previous research by examining four psychosocial manipulations under two levels of physical work exposure to gain a better understanding of how psychosocial manipulations change perceptions of the work environment.…”
Section: Introductionmentioning
confidence: 90%
“…Our task did not impose any major cognitive demands, which may be consistent with some industrial assembly tasks, while others may entail considerable requirements for decision making. Whether combined physical and mental demands would influence MAWP more than physical demands alone needs to be investigated further; some studies suggest that combined demands in upper extremity work may, indeed, lead to larger exposures in the shoulder region, and, therefore, likely to a different level of fatigue development and performance from that observed for only physical demands (Leyman, Mirka, Kaber, & Sommerich, 2004;Shaikh, Cobb, Golightly, Segal, & Haslegrave, 2012;Wang, Szeto, & Chan, 2011).…”
mentioning
confidence: 99%